2018
DOI: 10.1097/rhu.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sclerosis at an Intensive Care Unit

Abstract: The severity of the disease at ICU admission and comorbidity are independently associated with ICU-related mortality. Furthermore, the optimal management of SSc patients includes accurate detection of SSc-associated organ involvement. More studies involving this category of patients are needed to establish the best effective protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…32 reported mortality showed a very wide range of 16 to 89%, mainly depending on the investigated diseases and the reason for ICU admission. 14,16,[25][26][27][28][29]33,[36][37][38][39][40] Therefore, most of the publications are difficult to compare to our well-defined group of septic CTD patients. A study by Heijnen et al (n ¼ 86), for example, consisted of only 18.6% patients with a CTD and 60% were admitted to the ICU for infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 reported mortality showed a very wide range of 16 to 89%, mainly depending on the investigated diseases and the reason for ICU admission. 14,16,[25][26][27][28][29]33,[36][37][38][39][40] Therefore, most of the publications are difficult to compare to our well-defined group of septic CTD patients. A study by Heijnen et al (n ¼ 86), for example, consisted of only 18.6% patients with a CTD and 60% were admitted to the ICU for infection.…”
Section: Discussionmentioning
confidence: 99%
“…Bru ¨nnler et al 36 an ICU mortality of 43% in SSc patients, while the main causes of ICU admission were non-SSc-related (71.4%). 28 Shalev et al reviewed a small cohort of SSc patients (n ¼ 9) and found a high in-hospital mortality of 89%. 29 In this small group, sepsis was the main reason for ICU admission and death, with 62.5% of the deceased patients having a pulmonary involvement of the CTD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations